The serum proteome of nonalcoholic fatty liver disease: A multimodal approach to discovery of biomarkers of nonalcoholic steatohepatitis. Issue 10 (October 2014) - Miller, Michael H; Walsh, Shaun V; Atrih, Abdel; Huang, Jeffrey T‐J; Ferguson, Michael A J.; Dillon, John F
Abstract Background and Aim Nonalcoholic fatty liver disease (NAFLD) is a common condition affecting up to 25% of the developed world. It is a progressive disease, leading in some to the development of liver cirrhosis. Currently, accurate diagnosis and staging of this condition is only possible with histological examination of a liver biopsy. This gold standard test is neither suitable nor practical for large‐scale use as is necessary for a condition as common as NAFLD. The aim of this study is to describe the proteome of human NAFLD using two distinct shotgun proteomic methods, translating the findings into potential biomarkers of NAFLD. Methods Two distinct shotgun proteomic techniques (iTRAQ and label free) were used to describe the proteome of NAFLD. Thereafter, candidate biomarkers were selected for validation by ELISA. Results Over 550 protein identifications were made in the description of the NAFLD proteome. Several proteins were found to be significantly up/downregulated in nonalcoholic steatohepatitis compared with control, including apolipoprotein E (fold ratio of 1.67), insulin‐like growth factor‐binding protein 3 (IGFBP3, fold ratio of 1.642), Vitamin D‐binding protein (fold ratio of 4.587), and lymphocyte cytosolic protein1 (LCP1, fold ratio of 4.356). ELISA validation of a subset of these proteins confirms the validity of the proteomic studies and suggests possible new biomarkers of NAFLD. Conclusion Serum markers are able to distinguish between the stages of disease in NAFLD as well as detect the grade of fibrosis. Ultimately, noninvasive serum markers may replace liver biopsy in the investigation of patients with suspected NAFLD.